Evasive Maneuvers in Space Debris Environment and Technological Parameters - Jesus, Antonio D. C.; Ribeiro, Rafael S.; Rossi, Alessandro; Veira Neto, Ernesto [UNESP] (Hindawi Publishing Corporation, 2012)
We present a study of collisional dynamics between space debris and an operational vehicle in LEO. We adopted an approach based on the relative dynamics between the objects on a collisional course and with a short warning time and established a semianalytical solution for the final trajectories of these objects. Our results show that there are angular ranges in 3D, in addition to the initial conditions, that favor the collisions. These results allowed the investigation of a range of technological parameters for the spacecraft (e.g., fuel reserve) that allow a safe evasive maneuver (e.g., time available for the maneuver). The numerical model was tested for different values of the impact velocity and relative distance between the approaching objects.